Fourth-Party Evaluation of Third-Party Pro-social Help and Punishment: An ERP Study - Li, Jianbiao; Li, Shuaiqi; Wang, Pengcheng; Liu, Xiaoli; Zhu, Chengkang; Niu, Xiaofei; Wang, Guangrong; Yin, Xile (Frontiers in Psychology, 2018)
Pro-social behaviors have been adequately studied by neuroscientists. However, few neural studies have focused on the social evaluation of pro-social behaviors, and none has compared the neural correlates of different pro-social decision evaluations. By fourth-party evaluation of third-party punishment/help dictator game paradigm, we explored the third-party pro-social behaviors and derived feedback-related negativity (FRN) from the electroencephalogram. Different from previous event-related potentials (ERP) studies, we simultaneously focused on two different third-party pro-social behaviors, which were called third-party help and third-party punishment. For the first time, we compared the different neural processes of fourth-party evaluation on third-party help and punishment. Behavioral results showed that fourth-party bystanders appreciated the help behavior of the third party even more than the punishment behavior. ERP results revealed that fourth-party bystanders’ FRN amplitudes were modulated by the third-party behaviors. Under the assignment condition (70:30) with help/punishment magnitude 45 and (90:10) with magnitude 80, the third-party help elicited a larger FRN than third-party punishment; whereas under the condition (90:10) with help/punishment magnitude 45, the difference between FRN amplitudes disappeared. These results indicated that fourth-party bystanders ultimately agreed more with helpful third parties; however, after they witnessed the norm violation, they expected the third parties to punish the norm violators immediately. This phenomenon appears only when the third-party actors can achieve justice between norm violators and victims.